Genetic analysis of Fusarium wilt resistance in cowpea (Vigna unguiculata Walp.) - Omoigui, L.O.; Danmaigona, C.C.; Kamara, A.; Ekefan, E.J.; Timko, M.P. (Wiley, 2018)
This study investigated the inheritance of resistance to Fusarium oxysporum f.sp. tracheiphilum (Fot) in cowpea lines. Resistant and susceptible cowpea lines were crossed to develop F1, F2 and backcross populations. Reaction to Fot was evaluated in 2015 and 2016 using seed soak and modified root‐dip inoculation methods. The expression of resistance reaction in the F1 and segregation in F2 generations indicated the role of dominant gene controlling Fot in cowpea. These results were further supported by the result of backcross (BC1P1F1 and BC1P2F1) progeny tests. The backcross of F1 with the resistant parent produced progeny that were uniformly resistant, whereas backcross of F1 with the susceptible parent produced progeny that segregated into 1:1 ratio. The F2 segregation ratio in the reciprocal cross showed no evidence of maternal effect in the inheritance of the resistance. Allelism test suggests that the gene for resistance in TVu 134 was the same in TVu 410 and TVu 109‐1. We also identified an SSR marker, C13‐16, that cosegregated with the gene conferring resistance to Fot in cowpea.